The Ocean One hands: An adaptive design for robust marine manipulation. (February 2017) - Stuart, Hannah; Wang, Shiquan; Khatib, Oussama; Cutkosky, Mark R
Underactuated, compliant, tendon-driven robotic hands are suited for deep-sea exploration. The robust Ocean One hand design utilizes elastic finger joints and a spring transmission to achieve a variety of pinch and wrap grasps. Compliance in the fingers and transmission determines the degree of load-sharing among contacts and the hands' ability to secure irregularly shaped objects. However, it can also decrease external grasp stiffness and acquisition reliability. SimGrasp, a flexible dynamic hand simulator, enables parametric studies of the hand for acquisition and pull-out tests with varying transmission spring rates. In the present application, we take advantage of achieving different stiffnesses by reversing the direction of tendon windup using a torsional spring-loaded winch. With this provision, the hand can be relatively soft for handling delicate objects and stiff for tasks requiring strength. Two hands were field-tested as part of the Ocean One humanoid platform, which acquired a vase from the La Lune shipwreck site at a 91 m depth in the Mediterranean Sea.